Left-Sided Cardiac Valvulitis in Tristetraprolin-Deficient Mice: The Role of Tumor Necrosis Factor α - Ghosh, Sanjukta (American Society for Investigative Pathology, 2010)
Inflammation may play a role in the etiology of both degenerative and rheumatic cardiac valve diseases. We report here that mice deficient in tristetraprolin (TTP), a protein with known anti-inflammatory functions, develop severe left-sided cardiac valvulitis. TTP is an mRNA binding protein that inhibits inflammation by destabilizing the mRNA encoding tumor necrosis factor α (TNF). This leads in turn to a TNF-excess syndrome characterized by systemic inflammation. Evaluation of hearts from TTP(−/−) mice demonstrated gross thickening of the mitral and aortic but not the tricuspid or pulmonary valves, accompanied by inflammatory cell infiltrates. To determine whether TNF played a role in the development of this valvulitis, we examined mice deficient in both TNF receptors and in TTP; four of five of these mice exhibited no histological evidence of valvulitis, but one mouse had aortic valve leaflet thickening with a cellular infiltrate. Four additional mice had no external evidence of valvular thickening. Cardiac valves of transgenic mice expressing human TNF developed mild aortic valve leaflet edema without evidence of hypercellularity. Thus, TTP deficiency in mice leads to left-sided cardiac valvulitis with prominent inflammatory cell involvement, due, at least in part, to excess TNF. These findings support the potential involvement of TNF and inflammation in the development of cardiac valve disease in man.